Focusing on the 'human' in human capital : positive youth development as a foundation for maximising human capital investment - Krauss, Steven Eric...[et al.] (2007)
Argues that the positive youth development approach is an effective strategy for building human assets and competencies for maximising human capital, and turning inputs (training and education ) into future 'value added' for organisations, businesses and communitiies.